The versatility of algae in addressing the global sustainability challenges - Das, Bishnu Dev; Bhattarai, Ajaya (Frontiers in Bioengineering and Biotechnology, 2025)
Algae have developed into a sustainable and adaptable resource that can help with several global issues, such as resource depletion, environmental degradation, food security, climate change, and energy security. It explores the multifaceted potential of algae in addressing key global sustainability challenges—including climate change, resource depletion, environmental pollution, food insecurity, and energy demands—through biotechnological innovations. Chlorella, Nannochloropsis, Botryococcus, and Spirulina demonstrate exceptional efficiency in biomass production, carbon sequestration, nutrient recycling, and bioenergy generation. Objectives of this review include evaluating recent advances in algal-based wastewater remediation, biodiesel production, and circular bioeconomy strategies, with a focus on the integration of industrial waste streams like abattoir wastewater and crude glycerol. Notably, Chlorella sorokiniana has shown high potential for phycoremediation and biodiesel yield when cultivated in abattoir wastewater digestate (AWD), achieving up to 90% BBM replacement with enhanced lipid and carotenoid content. Similarly, the valorization of crude glycerol via microbial and insect-based systems underscores algae’s role in supporting low-carbon bioeconomies. In agriculture, macroalgae such as Asparagopsis taxiformis have significantly reduced enteric methane emissions in livestock, highlighting their utility in climate-smart farming. Despite these advances, the scalability and economic viability of algal technologies remain constrained by high production costs, energy-intensive processing, contamination risks, and regulatory limitations—especially in food and feed sectors. It advocates for targeted research into cost reduction, process optimization, and harmonized policy frameworks to unlock algae’s full potential. By addressing these challenges, algae can become central to sustainable development strategies, enabling effective transitions toward cleaner energy, healthier ecosystems, and resilient food systems.